Comparison of different disinfection protocols against contamination of ceramic surfaces with Klebsiella pneumoniae biofilm - Piletić Kaća; Mežnarić Silvestar; Keržić Eli; Oder Martina; Gobin Ivana (Arhiv za Higijenu Rada i Toksikologiju)
Environmental contamination with Klebsiella pneumoniae biofilm can be a source of healthcare-associated infections. Disinfection with various biocidal active substances is usually the method of choice to remove contamination with biofilm. In this study we tested 13 different disinfection protocols using gaseous ozone, citric acid, and three working concentrations of benzalkonium chloride-based professional disinfecting products on 24-hour-old biofilms formed by two K. pneumoniae strains on ceramic tiles. All tested protocols significantly reduced total bacterial counts compared to control, varying from a log10 CFU reduction factor of 1.4 to 5.6. Disinfection combining two or more biocidal active substances resulted in significantly better anti-biofilm efficacy than disinfection with single substances, and the most effective combination for both strains was that of citric acid, gaseous ozone, and benzalkonium chloride. This follow up study is limited to K. pneumoniae alone, and to overcome this limitation, future studies should include more bacterial species, both Gram-positive and Gramnegative, and more samples for us to find optimal disinfection protocols, applicable in real hospital settings.